The value of triglyceride glucose-body mass index, fasting blood glucose to HDL-C ratio, and platelet to HDL-C ratio in predicting abdominal aortic calcification in maintenance hemodialysis patients - Chen, Shanshan; Cao, Qianqian; Bu, Shuangshan; Xu, Lingyuan; Zhou, Zijun; Wu, Yuemeng; Zheng, Huanhuan (Renal failure, 2025)
The triglyceride glucose-body mass index (TyG-BMI), fasting blood glucose (FBG) to high-density lipoprotein cholesterol (HDL-C) ratio (GHR), and platelet (PLT) to HDL-C ratio (PHR) are well-established markers of insulin resistance (IR), closely linked to cardiovascular and cerebrovascular diseases. Abdominal aortic calcification (AAC), a key indicator of subclinical atherosclerotic, is highly prevalent in maintenance hemodialysis (MHD) patients. This study aimed to explore the cross-sectional relationship between these IR indices and AAC in MHD patients and identify the most reliable predictive marker. We recruited 391 MHD patients from two hemodialysis medical centers, with 297 meeting the inclusion criteria. AAC was detected via X-ray scanning of the lumbar spine, quantified by the Kauppila scoring system. Receiver operating characteristic (ROC) curve analysis determined optimal cutoff values for dividing the subjects into high-index and low-index groups. Multivariable logistic regression models evaluated the association between AAC and these IR indices. The prevalence of AAC in the whole group was 72.4%. The occurrence of AAC in the high-index group was significantly higher than that in the low-index group. Among the three IR indices, PHR demonstrated the highest predictive stability when integrated into a combined model. Subgroup analyses confirmed the robustness of this association across different age groups, sex, hypertension levels, comorbidities (CVD and stroke history), and smoking status. TyG-BMI, GHR and PHR were independently associated with the presence of AAC among MHD patients. Notably, PHR showed the strongest correlation with AAC, suggesting its potential clinical utility in risk stratification.